2002
DOI: 10.1177/1534735402001001003
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Effects of Vitexina for Breast Cancer Patients Undergoing Radiotherapy With Cobalt-60

Abstract: Vitexina, a product containing the flavonoid vitexin as the main component, is derived from a plant, Vigna radiata (L.), that has been traditionally used in Vietnam for detoxification. This remedy is also used to treat the symptoms of conditions classified as "hot" in traditional medicine. The present study is a randomized, placebo-controlled comparative clinical trial for investigating the radioprotective effects of Vitexina for breast cancer patients undergoing radiotherapy with cobalt-60. No relevant weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Recently we showed the following rank of the antioxidant activity of flavone C -glucosides as compared to quercetin: quercetin ≥ homoorientin > orientin > isovitexin > vitexin [ 5 ]. Various biological and pharmacological activities have been attributed to these compounds, such as hypotensive, anti-inflammatory, antispasmodic [ 25 ], antimicrobial [ 26 ], radioprotective effects [ 27 ] and anti-glycation activities [ 28 ]. Therefore, preferentially accumulation of flavone C -glucosides in unripe seeds collected from common buckwheat at 48 DAS is an important outcome of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we showed the following rank of the antioxidant activity of flavone C -glucosides as compared to quercetin: quercetin ≥ homoorientin > orientin > isovitexin > vitexin [ 5 ]. Various biological and pharmacological activities have been attributed to these compounds, such as hypotensive, anti-inflammatory, antispasmodic [ 25 ], antimicrobial [ 26 ], radioprotective effects [ 27 ] and anti-glycation activities [ 28 ]. Therefore, preferentially accumulation of flavone C -glucosides in unripe seeds collected from common buckwheat at 48 DAS is an important outcome of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that many flavonoid compounds exert protective effects against the development of certain cancers,1 cardiovascular risk,2 inflammatory diseases,3 coronary heart disease, and strokes 4. Other pharmacological activities have also been attributed to flavonoids, including antimicrobial,5 antioxidant,6, 7 free radical scavenging properties,8 and radioprotective effects 9…”
Section: Subclasses Of Flavonoidsmentioning
confidence: 99%
“…Various biological and pharmacological activities have been attributed to these compounds, such as hypotensive, anti-inflammatory, antispasmodic, antimicrobial, antioxidant/free radical scavenging, radioprotective effects, and anti-glycation activities. [48][49][50] Advanced glycation endproducts (AGEs) accumulation has been implicated as a major pathogenic process in diabetes, atherosclerosis, Alzheimer's disease, and aging. [25] The BSA-glucose model adopted in this study provides a useful tool for the evaluation of the activity of buckwheat hull tea and green tea as glycation inhibitors.…”
Section: Inhibitory Effect Of Buckwheat Hull Tea Infusion and Green Tmentioning
confidence: 99%